Aggressive Natural Killer Cell Leukemia in an Adolescent Patient: A Case Report and Literature Review - Yang, Rong; Ai, Yuan; Liu, Chuan; Lu, Xiaoxi (Frontiers in Pediatrics, 2022)
Aggressive natural killer cell leukemia (ANKL) is a rare malignant tumor, especially uncommon in children. ANKL has very aggressive clinical course and bad prognosis and is usually caused by Epstein-Barr virus infection. Here we report an ANKL in adolescent whose clinical presentation was highly aggressive and response to L-asparaginase containing chemotherapy was very bad. When an hemophagocytic lymphohistiocytosis patient is complicated with liver dysfunction and disseminated intravascular coagulation, diagnosis of ANKL should be considered. Early-onset Flow cytometry of peripheral blood and bone marrow help make the diagnosis.